the Assessment Of Health Care Of Hypothyroidism Patients Using Levels Of calcium and Vitamin D (Journal of Academic Research, 2025)
Background and purpose: Hypothyroidism is a condition that occurs when the thyroid gland does not produce enough hormones to meet the body’s needs, which leads to a slowdown in some body functions. The study was conducted to evaluate hypothyroidism and its relationship to vitamin D and calcium deficiency                                                                                                                                                     Method and materials: The study group included children [n=20], men [n=20], and women [n=20] as a group of cases. The levels of TSH, Ca, and Vit D were measured. This study was conducted in the Zliten Teaching Hospital                                                                                                                                        Results: present study showed non-significant correlation for child patients(0.05)were the averaged vit D (0.043) and calcium (0.025) also into showed female patients(0.0527)were the averaged vit D (0.034)and calcium (0.025) also into showed male patients (0.05) were the averaged vit D (0.05) and calcium.
Keywords: hypothyroidism; vitamin D; calcium